PENGELOLAAN EKOSISTEM MANGROVE PULAU-PULAU KECIL TAMAN NASIONAL BUNAKEN BERBASIS KERENTANAN - N.W. Schaduw, Joshian; Yulianda, Fredinan; G. Bengen, Dietriech; Setyobudiandi, Isdradjad (FAPETKAN UNTAD, 2011)
Mangrove ecosystem has many functions for coastal area, such as, functions of ecology, social and economic. These functions lead to systemic impact toward other coastal ecosystem environment and human life. Through mitigation, this function can be optimized to minimize the degradation of small island environment. This research analyzed the existing condition of mangrove ecosystem, vulnerability of small islands, and also pattern and management strategy of mitigation based on mangrove ecosystem. This research used both primary and secondary data. Primary data was gathered by sampling field observation, questioner, open interview and in-depth interview in the research area. Secondary data was gathered by literature review and from related institutions. Vulnerability index was analyzed using multi dimensional scaling method whereas vulnerability mapping was analyzed by analysis of geographic information system using the software Archieve Project 3.3. The results of this research was the mangrove ecosystem of small islands in Taman Nasional Bunaken needs to be better managing, considering the increasing rate of degradation and threats to these ecosystems. Nain Island was the most vulnerable island toward the threat of damaging ecosystems by human activities and natural factors. Management scheme which can accommodate a variety of problems faced by the mangrove ecosystems of small islands was collaborative management by the government as the leading sector with the highest priority on the management of the ecological dimension. Key words : Management, mangrove ecosystem, small island, vulnerability.